2017
DOI: 10.4103/ijo.ijo_191_17
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in the intron of TCF4 gene to late-onset Fuchs endothelial corneal dystrophy: An Indian cohort study

Abstract: Purpose:Fuchs endothelial corneal dystrophy (FECD) is a progressive degenerative disease of the corneal endothelium. It is genetically heterogeneous and follows either an autosomal dominant or sporadic pattern of inheritance. Here, we have explored the association of four previously reported intronic single nucleotide polymorphisms and intronic CTG repeat expansions in TCF4 gene to FECD in an Indian cohort.Methods:The cohort consisting of 52 sporadic late-onset cases, 5 early-onset cases, and 148 controls was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…A comparison of the role of ZEB1 across multiple ethnicities shows that the contribution of this gene in our Indian population is concurrent with other reports (Rao et al, 2018). In another study it was found that the single nucleotide polymorphisms (SNPs) of TCF4 gene, rs613872 and rs1759573 were associated with a higher risk of sporadic late-onset FECD in Indian patients (Rao, Tharigopala, Rachapalli, Rajagopal, & Soumittra, 2017).…”
Section: Landscape and Demographics In Indiasupporting
confidence: 86%
“…A comparison of the role of ZEB1 across multiple ethnicities shows that the contribution of this gene in our Indian population is concurrent with other reports (Rao et al, 2018). In another study it was found that the single nucleotide polymorphisms (SNPs) of TCF4 gene, rs613872 and rs1759573 were associated with a higher risk of sporadic late-onset FECD in Indian patients (Rao, Tharigopala, Rachapalli, Rajagopal, & Soumittra, 2017).…”
Section: Landscape and Demographics In Indiasupporting
confidence: 86%
“…Another important aspect of disease variation is the recognized fact that women more commonly express FECD and in general have more severe clinical presentation. This trend is consistent across diverse populations and holds true for groups with and without CTG18.1 repeat expansion ( Kuot et al, 2017 ; Nakano et al, 2015 ; Nanda et al, 2014 ; Okumura et al, 2019c ; Rao et al, 2017 ; Skorodumova et al, 2018 ; Soliman et al, 2015 ; Vasanth et al, 2015 ; Wieben et al, 2012 ; Zarouchlioti et al, 2018 ). While our current understanding of FECD lends essentially no insight into this observation, several possible explanations exist.…”
Section: Future Perspectivessupporting
confidence: 63%
“…Interestingly, the correlation between CTG18.1 expansion and FECD is also striking, although typically lower, in other non-Caucasian ethnic groups investigated to date. This includes African Americans (35%) ( Eghrari et al, 2017a ), Indians (17% and 34%) ( Nanda et al, 2014 ; Rao et al, 2017 ), Japanese (26%) ( Nakano et al, 2015 ), Singaporean Chinese (44%) ( Xing et al, 2014 ), and Thai (39%) ( Okumura et al, 2019c ). Notably, CTG18.1 genotyping studies have consistently identified a bimodal distribution of repeat lengths, with the vast majority of patients typically harbouring repeat sizes of <30 or >50 ( Zarouchlioti et al, 2018 ).…”
Section: Genetic Association Of Tcf4 and Fecdmentioning
confidence: 99%
See 1 more Smart Citation
“…However later, a much stronger association was found to an expansion of cytosine-thymine-guanine (CTG) n repeat, known as CTG18.1 [ 5 ], in intron 3 of the TCF4 gene [ 6 ]. Currently, association of the TCF4 repeat expansion ( n > 50) and FECD has been reported in several populations [ 7 , 8 , 9 , 10 , 11 ]. In other studies, association of FECD and (CTG) n repeat length over 40 has also been shown [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%